1998
DOI: 10.1095/biolreprod59.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Bull Sperm Binding to Oviductal Epithelium Is Mediated by a Ca2+-Dependent Lectin on Sperm That Recognizes Lewis-a Trisaccharide1

Abstract: Sperm binding to oviductal epithelium produces a reservoir in vivo that may serve to maintain sperm fertility and provide sperm for fertilization when ovulation occurs. Previously, it was determined that bull sperm binding could be blocked by fucoidan and its component fucose; furthermore, treatment of epithelium with fucosidase prevented binding. The present study was conducted to further characterize binding. Because fucose would probably be present on the epithelium as part of oligosaccharide moieties of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 33 publications
(45 reference statements)
3
50
0
3
Order By: Relevance
“…However, evidence from other studies indicates the involvement of glycoproteins on the oviductal epithelial cell surface in conjunction with sperm plasma membrane carbohydrate recognition domains. Adherence of Lewis-a trisaccharide to acrosome intact bull spermatozoa (Suarez et al, 1998) and fetuin to hamster spermatozoa (DeMott et al, 1995) interfered with spermoviductal epithelial cell binding. In support of this finding, enzymatic removal of fucose residues from bovine oviductal epithelia resulted in a marked reduction in sperm binding (Lefebvre et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, evidence from other studies indicates the involvement of glycoproteins on the oviductal epithelial cell surface in conjunction with sperm plasma membrane carbohydrate recognition domains. Adherence of Lewis-a trisaccharide to acrosome intact bull spermatozoa (Suarez et al, 1998) and fetuin to hamster spermatozoa (DeMott et al, 1995) interfered with spermoviductal epithelial cell binding. In support of this finding, enzymatic removal of fucose residues from bovine oviductal epithelia resulted in a marked reduction in sperm binding (Lefebvre et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The effective inhibition of sperm-oviductal epithelial cell binding by larger carbohydrate molecules has been demonstrated in other species. In cattle (Lefebvre et al, 1997;Suarez et al, 1998), hamsters (DeMott et al, 1995 and horses (Dobrinski et al, 1996a), glycoproteins inhibit binding more effectively than their monosaccharide subunits. Ahuja (1985) suggested that these differences may be due to a decreased binding affinity of monosaccharides in comparison to oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Xenopus, a CRISP-like protein in the egg jelly acts as a sperm attractant (Olson et al, 2001). AAEL001121 and AAEL10596 are predicted lectins, a family of proteins which have been found to influence gamete interactions during fertilization (Romero et al, 1997) and regulate sperm binding to the female oviduct (Suarez et al, 1998) in mammals and mediate the release of sperm from female sperm storage organs in D. melanogaster (Ravi Ram and Wolfner, In press). …”
Section: 5d Sperm Interaction-sixmentioning
confidence: 99%